Position paper on olfactory dysfunction - Hummel, T; Whitcroft, K L; Andrews, P; Altundag, A; Cinghi, C; Costanzo, R M; Damm, M; Frasnelli, J; Gudziol, H; Gupta, N; Haehner, A; Holbrook, E; et al. (Rhinology, 2016)
BACKGROUND: Olfactory dysfunction is an increasingly recognised condition, associated with reduced quality of life and major health outcomes such as neurodegeneration and death. However, translational research in this field is limited by heterogeneity in methodological approach, including definitions of impairment, improvement and appropriate assessment techniques. Accordingly, effective treatments for smell loss are limited. In an effort to encourage high quality and comparable work in this field, among others, we propose the following ideas and recommendations. Whilst the full set of recommendations are outlined in the main document, points include the following: - Patients with suspected olfactory loss should undergo a full examination of the head and neck, including rigid nasal endoscopy with small diameter endoscopes. - Subjective olfactory assessment should not be undertaken in isolation, given its poor reliability. - Psychophysical assessment tools used in clinical and research settings should include reliable and validated tests of odour threshold, and/or one of odour identification or discrimination. - Comprehensive chemosensory assessment should include gustatory screening. - Smell training can be helpful in patients with olfactory loss of several aetiologies. CONCLUSIONS: We hope the current manuscript will encourage clinicians and researchers to adopt a common language, and in so doing, increase the methodological quality, consistency and generalisability of work in this field.